Reading Experimental Writing - Colby, Georgina (Edinburgh University Press, 2022)
Explores the challenges and significance of experimental writingOffers a forum for reflecting on the significance of avant-garde writing for the twenty-first centuryExplores the way in which contemporary experimental writers engage with socio-political issuesUtilizes unpublished archive materials bringing to light a number of previously unpublished worksIncludes innovative readings of significant avant-garde writers previously neglected in the critical canonBringing together internationally leading scholars whose work engages with the continued importance of literary experiment, this book takes up the question of 'reading' in the contemporary climate from culturally and linguistically diverse perspectives. New reading practices are both offered and traced in avant-garde writers across the twentieth and twenty-first centuries, including John Cage, Kathy Acker, Charles Bernstein, Erica Hunt, Theresa Hak Kyung Cha, Rosmarie Waldrop, Joan Retallack, M. NourbeSe Philip, Caroline Bergvall, Uljana Wolf, Samantha Gorman and Dave Jhave Johnston, among others. Exploring the socio-political significance of literary experiment, the book yields new critical approaches to reading avant-garde writing
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Apr 2022)
Keywords: Literary Studies; LITERARY CRITICISM / American / General; Literature, Experimental -- History and criticism; Literature, Modern -- 20th century -- History and criticism; Literature, Modern -- 21st century -- History and criticism